The Myth of the Ideal Graduate: A Critical Perspective on Narrative Identity Formation in a Cohort of Graduates - Smith, Leo; Gaardsdal Løth, Ida; Lasskogen, Sara (Communication & Language at Work, 2022)
Power is a defining feature of organizational life in general and in organisational socialisation in particular. In this study we aim at developing a deeper understanding of the tension between newcomers’ search for expressing their authentic selves and the pressure to comply with what we call the myth of the ideal employee. We conceptualise the myth of the ideal employee as a dominant narrative that structures the process of membership negotiation as discussed by McPhee and Zaug (2000). Drawing on Alvesson and Wilmott (2002) and Ashforth and Schinoff (2016), we conceptualise the process as identity regulation pertaining to how newly hired graduates come to define “who they are” in a large corporation. We present findings from a longitudinal, qualitative study with data consisting of sixty-two interviews with a cohort of graduates in a corporate graduate programme. Over a period of six months, three interviews were conducted with each graduate; one before entering the organization, one after three months, and one after six months. As we conceptualise identity as embedded in narrative, the data has been analyzed through a narrative analysis, using Greimas’ actantial model. Our analysis dives into each interview round as well as narrative trajectories across interview rounds with a central emphasis on identity regulation and becoming a member. The findings demonstrate how the myth constrains graduates to match a specific narrative identity and ideology in accordance with the organization’s own and how the newcomers strategize to establish a particular presence in the organization. It also reveals small but consequential attempts to “stay true to oneself”, thus unravelling the complex, ongoing negotiation of “who one is” and the key stakeholders involved.